Sosialisasi Tentang Membangun Ketahanan Diri Remaja Dalam Menanggulangi Penyalahgunaan Narkoba Sebagai Upaya Menjaga Ketahanan Nasional Di Sekolah Menengah Atas Kartika 1-5 Kota Padang - Sry Wahyuni; Elwidarifa Marwenny; Muhammad Nazif; Salsabilla Afrilisya; Azella Widi Syahrani; Salmi Agustri; Fauzan Mukhlisin (GLOBAL SCIENTS PUBLISHER, 2025)
Teenagers are a group that is vulnerable to the dangers of drug encryption which can have a significant impact on individual resilience and national security. This outreach activity was carried out as an effort to build the self-resilience of high school students at SMA Kartika 1-5 Padang to prevent drug prevention. Through the outreach program, it is hoped that it can increase students’ awareness, knowledge and ability to fight the effects of drugs. The methods used include lectures, group discussions, and motivational activities, which involve collaboration between teachers and the Law Studies Study Program team, FHISH Unidha. The results show an increase in students’ understanding of the material presented. Further implementation and ensuring similar development programs are recommended for wider impact.